2018
DOI: 10.4236/psych.2018.93030
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, Social Support, Pride, and Contentment as Differential Predictors of Resilience and Life Satisfaction in Emerging Adulthood

Abstract: This study addressed the possible differential impact of various types of spirituality, perceived social support, and positive emotions on resilience and life satisfaction in emerging adulthood. , 2006) to assess various positive emotions. As hypothesized, intrapersonal spirituality, perceived social support, and positive emotions predicted both resilience and life satisfaction, but differed in their relative contributions to each type of well-being. Intrapersonal spirituality and pride predicted resilience,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
5
0
2
Order By: Relevance
“…In the same light as the previous paragraph, Gerson [60] reported that spirituality predicted PSS, resilience, and life satisfaction and added that spirituality was a more robust predictor of resilience than PSS, which required positive emotions to mediate its contribution on resilience. Confirming that, Dey et al [61] advocated that a greater level of spirituality predicted greater resilience, which explains the further link to greater levels of life satisfaction and positive affect.…”
Section: Introductionmentioning
confidence: 71%
“…In the same light as the previous paragraph, Gerson [60] reported that spirituality predicted PSS, resilience, and life satisfaction and added that spirituality was a more robust predictor of resilience than PSS, which required positive emotions to mediate its contribution on resilience. Confirming that, Dey et al [61] advocated that a greater level of spirituality predicted greater resilience, which explains the further link to greater levels of life satisfaction and positive affect.…”
Section: Introductionmentioning
confidence: 71%
“…Among the range of factors associated with life satisfaction, studies have identified the influence of perceived support within the family context (Edwards & Lopez, 2006; Huang et al, 2015). Among emerging adults, determinants of life satisfaction include identity development, the endorsement of adulthood-related duties and roles, perceived social support, social skills, and a sense of competence (Gallagher & Vella-Brodrick, 2008; Gerson, 2018; Piumatti, 2017). Also, studies have shown how supportive social and family relationships are positively related to well-being, namely life satisfaction and satisfaction with the family (Crocetti & Meeus, 2014; Curran & Yoshimura, 2016; Diener & Diener, 1995; Jewell & Kambhampati, 2015).…”
Section: Grandparenthood Family Satisfaction and Life Satisfaction mentioning
confidence: 99%
“…As was presented in the EU Social Insecurities and Resilience Report [ 51 ], people who have low levels of social insecurities more often report high levels of resilience. In recent psychological research [ 52 ], contentment was also directly associated with both resilience and life satisfaction and mediated the relationship between these 2 aspects of well-being. Details and further analysis is presented in Multimedia Appendix 1 .…”
Section: Resultsmentioning
confidence: 99%